Gonorrhea in Adolescents: Risk Factors and Prevention: A Literature Review - Jasmine, Ayesha; Verawaty, Liana (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Abstract Background. Gonorrhea is one of the most common sexually transmitted infections (STIs), especially in developing countries like Indonesia. Adolescents are vulnerable to this disease, mainly due to risk factors involving biological, social, and behavioral aspects. This study aims to explore the risk factors of gonorrhea in adolescents and the prevention efforts that have been and can be done. Methods. Through a literature review of 10 articles in the last five years, it was found that young age, number of sexual partners, use of psychotropic drugs, and low socioeconomic and educational levels are the main causes of high gonorrhea cases. Discussion. In addition, globalization and changing social norms also contribute to the increase in risky behavior among adolescents. Gonorrhea prevention efforts can be done through comprehensive sex education, consistent condom use, and empowerment of adolescents through intervention programs such as ABC (Abstinence, Be Faithful, Use a Condom). Conclusion. By increasing access to reproductive health services and reducing stigma towards STIs, it is hoped that the prevalence of gonorrhea in adolescents can be reduced.